2014
DOI: 10.4049/jimmunol.1302771
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Donor Apoptotic Cell Infusions Induce IFN-γ–Producing Myeloid-Derived Suppressor Cells for Cardiac Allograft Protection

Abstract: We have previously shown that preemptive infusion of apoptotic donor splenocytes treated with the chemical cross-linker ethylcarbodiimide (ECDI-SPs) induces long-term allograft survival in full MHC-mismatched models of allogeneic islet and cardiac transplantation. The role of myeloid derived suppressor cells (MDSCs) in the graft protection provided by ECDI-SPs is unclear. In this study, we demonstrate that infusions of ECDI-SPs increase two populations of CD11b+ cells in the spleen that phenotypically resemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 46 publications
(76 reference statements)
0
35
0
Order By: Relevance
“…These cells are typically CD11b + Gr1 + in mouse models of transplantation and are considerably less well defined in human recipients of transplantation; they were only recently identified in renal transplant patients as CD11b + CD33 + HLA-DR − cells with variable levels of expression of CD14 and CD16, underscoring their phenotypic heterogeneity (118121). They mediate suppression by several mechanisms, including inhibition of cytotoxic T cell responses by generation of reactive oxygen species and IL-10, depletion of L-arginine via arginase 1 and inducible nitric oxide synthase, depletion of tryptophan via indoleamine 2,3-dioxygenase (IDO), and promotion of T reg s via IFN-γ-dependent pathways.…”
Section: Tolerance In Cell Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells are typically CD11b + Gr1 + in mouse models of transplantation and are considerably less well defined in human recipients of transplantation; they were only recently identified in renal transplant patients as CD11b + CD33 + HLA-DR − cells with variable levels of expression of CD14 and CD16, underscoring their phenotypic heterogeneity (118121). They mediate suppression by several mechanisms, including inhibition of cytotoxic T cell responses by generation of reactive oxygen species and IL-10, depletion of L-arginine via arginase 1 and inducible nitric oxide synthase, depletion of tryptophan via indoleamine 2,3-dioxygenase (IDO), and promotion of T reg s via IFN-γ-dependent pathways.…”
Section: Tolerance In Cell Transplantationmentioning
confidence: 99%
“…Moreover, MDSCs were present in the cardiac allograft and suppressed the infiltration of CD8 + T cells and other effectors. MDSCs present in the graft also produced IL-10 and recruited T reg s in a CCL4-dependent manner, and depletion of MDSCs restored CD8 + T cell infiltration and graft rejection (121). …”
Section: Tolerance In Cell Transplantationmentioning
confidence: 99%
“…This result suggested that mobilization of bone marrow CD11b+CD115+Gr-1+ MDSCs under sterile inflammatory conditions could induce indefinite cardiac allograft survival. In another study, Luo's group demonstrated the expansion of two subpopulations of MDSCs induced by donor splenocytes treated with the chemical cross-linker ethylcarbodiimide (ECDI-SPs) was important for cardiac allograft protection [48]. Lastly, mammalian target of rapamycin (mTOR) inhibitors are the main immunosuppressive drugs for organ transplant recipients.…”
Section: Induction Of Transplant Tolerance By Mdscsmentioning
confidence: 99%
“…Moreover, MDSCs were found to be present in the cardiac allograft and suppressed the infiltration of CD8 + T cells and other effectors. MDSCs present in the graft were also found to produce IL-10 and to recruit T REGS in a CCL4-dependent manner, and depletion of MDSCs restored CD8 + T cell infiltration and graft rejection (87). Thus, a critical role for MDSCs in allo-ECDI-SP therapy may be the recruitment of T REGS into the graft, which subsequently suppress graft infiltration by CD8 + T cells.…”
Section: Regulatory Cells In Ecdi-treated Cell Tolerancementioning
confidence: 99%